Penerapan Akupresur Sanyinjiao (SP 6) dan Hegu (LI 4) Pada Penurunan Intensitas Nyeri Persalinan Kala 1 Fase Aktif Di Puskemas X - intan yusita; Yanyan Mulyani; Nuraini Dwi Arianti (NHM PRESS, 2021)
Labor is a physiological thing for every pregnant woman during the delivery process, the mother will experience nerve compression so that she feels the sensation of pain that is felt during painful contractions that will make her feel tired and afraid. There are many ways to reduce pain, including using non-pharmacological methods through acupressure, breath relaxation, etc. the Mother complains of pain during labor. This study aims to provide integrated care in pregnancy and childbirth with the application of acupressure on labor pain at X Health Center Bandung. This type of research is descriptive with a continuity of care approach through a case study with a sample of 3 women giving birth with complaints of labor pain in the active phase of the first stage, the sampling method is purposive sampling. Each mother in labor applied acupressure techniques for 6 cycles bilaterally at points SP 6 and LI 4. Pain assessment was carried out on respondents before and after the intervention. Based on the measurement results of the Numeric Rating Scale (NRS) pain scale, it was found that the respondents said that after the acupressure technique was performed at the point of delivery, the pain was reduced during the labor process. However, there are several factors such as age, coping mechanisms, environmental support, and so on. So it can be concluded that acupressure is effective in reducing pain during labor, especially in the first stage of the active phase and it is hoped that acupressure can be applied to help reduce labor pain to be comfortable.